NIMG-24. RANO CRITERIA DETECTS EARLY PROGRESSION SOONER THAN MODIFIED RANO CRITERIA IN PATIENTS WITH NEWLY DIAGNOSED GLIOBLASTOMA. (12th November 2021) - Youssef, Gilbert; Lim-Fat, Mary Jane; Bay, Camden; Arnaout, Omar; Bi, Wenya Linda; Cagney, Daniel; DeSalvo, Matthew; Castro, L Nicolas Gonzalez; Guenette, Jeffrey; Lee, Eudocia Quant; McFaline-Figueroa, J Ricardo; Potter, Christopher; et al.
Abstract: BACKGROUND: Accurate response criteria are crucial for determining treatment efficacy. The response assessment in neuro-oncology (RANO) criteria was developed to standardize response assessment in neuro-oncology. Modified RANO (m-RANO) criteria were recently proposed to address some limitations of the initial criteria including the use of a post-radiation baseline and an additional scan to confirm progression. We sought to identify differences in the association of progression-free survival (PFS) and overall survival (OS) using RANO and m-RANO criteria. METHODS: We conducted a retrospective review of newly diagnosed glioblastoma (GBM) patients treated at Dana-Farber Cancer Institute from January 2013 until December 2019. Patients with available clinical and imaging data obtained before initiation of treatment, after radiation completion and at intervals of 1 to 3 months were included. MRIs were evaluated by two independent readers, and PD dates determined using RANO and m-RANO criteria. RESULTS: 552 patients were included. 97.1% of the tumors were IDH wild-type. MGMT promoter was unmethylated in 51.4%, methylated in 35.1% and undetermined in 8.5%. Median OS among patients was 18.1 months. 72 patients (13%) did not have PD at the end of the study. 83 patients had treatment change while being clinically stable and without a confirmation scan and were excluded from the final analysis. PFS was 8.2 months with RANO and 8.4 months with mRANO. Difference in PD dates between RANO and m-RANO was detected in 76 patients (14%), where PFS was 3.5 months with RANO and 5.1 months with m-RANO. These patients had a worse median OS than those with identical RANO and m-RANO PD dates (15.2 vs. 22.4 months, p< 0.0001). CONCLUSION: RANO and m-RANO criteria resulted in identical PFS for most patients. 14% of patients had discordant PD dates and a worse prognosis. These patients progressed early, and their PD was identified sooner with RANO criteria.